Cultural pluralism increases difficulties in learning experiences yet advances identity formation for Muslim Arab female students at higher education institutions in Israel. (19th August 2014) - Arar, Khalid Husny; Masry-Herzalah, Asmahan; Blessinger, Patrick
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose This paper examines how learning experiences are shaped for Arab Muslim women students by the different educational approaches (teaching style, relations with lecturers and types of knowledge) and extent of cultural pluralism in three different Higher Education campuses in Israel. Design/methodology/approach To clarify these issues we conducted narrative interviews with twelve Arab Muslim women students in the Hebrew University and in two academic colleges. Significant differences were found in the women's experiences between the university and the two academic colleges. Findings Arab women had difficulty integrating in the university in contrast to a supportive more familiar environment in the colleges. The different environments also had different implications for the women's identity formation. The findings indicate that since Arab women students have specific needs stemming from their different socio-cultural background. Originality/value They should be assisted in their integration in academic courses with preparatory instruction and guidance. Implications for minority students in different HE campuses are discussed.